NOVEL BIOMATERIAL ASSISTED DRUG DELIVERY SYSTEMS FOR THE MANAGEMENT OF ORAL DISEASES–FUTURE THERAPEUTIC APPROACHES - CHANDRAN, MRIDULA R.; USHA, R. (International Journal of Applied Pharmaceutics, 2024)
Oral health is integral to maintaining systemic health as the mouth and oral cavity connect our digestive system with the external environment. The incidence of oro-dental disorders has been emerging as a serious threat to the healthcare sector owing to the increasing complexity of oral microbiome. Conventional treatment modalities are often limited by drug resistance and unwanted inflammatory responses. Recently, therapeutic strategies that can reinstate microbial homeostasis in the oral microenvironment have been implicated in the management of odontogenic infections. Biomaterial-based drug delivery systems, including nanocarriers, dendrimers, hydrogels, oral thin films, oral patches, and other stimuli-responsive polymeric systems, facilitate targeted administration of antimicrobials and anti-inflammatory agents to the site of infection. Bio adhesivity of the polymeric carriers facilitates faster disintegration and accurate dosing of the pharmacological agent to the target site. Moreover, restorative dentistry has been revolutionized by the advent of bio-functional templates that offer improved osseointegration and long-term stability of implants. A comprehensive review of the potential applications of biomaterial-mediated therapeutic strategies in the management of caries, peri-implantitis, periodontitis, and other oro-dental infections is explored here.